2016
DOI: 10.1111/1460-6984.12268
|View full text |Cite
|
Sign up to set email alerts
|

Communicative effectiveness of pantomime gesture in people with aphasia

Abstract: Background: Human communication occurs through both verbal and visual/motoric modalities. Simultaneous conversational speech and gesture occurs across all cultures and age groups. When verbal communication is compromised, more of the communicative load can be transferred to the gesture modality. Although people with aphasia produce meaning-laden gestures, the communicative value of these has not been adequately investigated. Aims: To investigate the communicative effectiveness of pantomime gesture produced spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 24 publications
(57 reference statements)
4
37
0
1
Order By: Relevance
“…Our work has further implications for clinical practice, where it can be applied to areas such as communication disorders. Research has shown that people with aphasia use gestures, including pantomimes, to supplement the semantic content of their speech (DeBeer et al, 2015;Rose, Mok, & Sekine, 2017). Knowledge of which features contribute to semantically recognizable gestures could, therefore, be applied to developing therapies for more effective pantomime use and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Our work has further implications for clinical practice, where it can be applied to areas such as communication disorders. Research has shown that people with aphasia use gestures, including pantomimes, to supplement the semantic content of their speech (DeBeer et al, 2015;Rose, Mok, & Sekine, 2017). Knowledge of which features contribute to semantically recognizable gestures could, therefore, be applied to developing therapies for more effective pantomime use and understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the earlier research on PWA's gesturing focused on co-speech gestures (e.g., Cocks et al 2013, Coelho 1990, Hogrefe et al 2012 with only a few studies looking at the comprehensibility of these gestures. These studies showed that information in PWA's co-speech gestures can help interlocutors in identifying the message PWA try to convey, as PWA's gestures often convey information not conveyed in speech (de Beer et al 2017, Mol et al 2013, Rose et al 2016.…”
Section: Pantomime's Comprehensibilitymentioning
confidence: 99%
“…The authors concluded that PWA compensate for their verbal limitations by employing gestures. Also using a rating paradigm, Rose, Mok, and Sekine (2017), focusing exclusively on pantomime gestures, confirmed the finding that PWA use gestures to express information that complements verbal speech. They compared the information expressed by both gesture and speech in isolation and by both channels in combination.…”
Section: Introductionmentioning
confidence: 59%
“…The combined and therefore most natural signal, consisting of both gesture and speech, was found to be most informative to the listeners. Following up on the study by Rose et al (2017), De Beer et al (2017) investigated the communicative role of three different gesture types, namely pantomimes, emblems, and referential gestures (a category containing both iconic and deictic gestures) in extracts from spontaneous conversations. The results revealed that the naive raters understood the messages expressed by the PWA of varying severities more accurately when they were expressed using gesture and speech as opposed to speech alone.…”
Section: Introductionmentioning
confidence: 99%